„Ziemia krakowska gościnnie i serdecznie przyjmuje premiera Fidela Castro”. Wizyta kubańskiej delegacji partyjno-rządowej w Krakowie w czerwcu 1972 r. w relacji czołowych dzienników lokalnych .......... 217 - Musiał, Marcin (Od Sumeru do zimnej wojny, 2025)
“THE KRAKÓW REGION WELCOMES PRIME MINISTER FIDEL CASTRO WITH HOSPITALITY AND WARMTH.” THE VISIT OF THE CUBAN PARTY AND GOVERNMENT DELEGATION TO KRAKÓW IN JUNE 1972 AS REPORTED BY LEADING LOCAL NEWSPAPERSThe article deals with Fidel Castro’s visit to Poland in June 1972. The author’s main goal was to expose the press coverage of this event. The main primary sources used during writing were Krakow’s daily journals such as “Dziennik Polski”, “Echo Krakowa”, and “Gazeta Krakowska”. Due to the nature of these press titles (regional character, close ties with the communist authorities) the author’s goal was to depict Castro’s stay in Krakow, taking into account the propaganda dimension of the reports presented to readers.